A head start in higher education: the effect of a transition intervention on interaction, sense of belonging, and academic performance. Issue 4 (2nd April 2020) - van Herpen, Sanne G. A.; Meeuwisse, Marieke; Hofman, W. H. Adriaan; Severiens, Sabine E.
ABSTRACT: Given the challenging transition from secondary school into higher education, this quasi-experimental study measured the effects of a pre-academic programme (i.e. before starting at university) on student–faculty interactions, student–peer interactions, sense of belonging, and first-year academic performance. Fifty-eight first-year students participated in a pre-academic programme (i.e. the experimental group) focused on changing their perceptions of effective learning behaviour to enhance high-quality interaction with peers and faculty, their sense of belonging, and academic performance. A control group comprised 237 first-year students who did not attend the programme. Participation in the programme enhanced formal student–faculty and student-peer interactions, as well as informal student-peer interactions. No effect was found on sense of belonging. Furthermore, participation in the programme enhanced students' attained grade during the first course and enhanced their first-year cumulative GPA. The results suggest that participation in the pre-academic programme could give students a head start in higher education.